Projectional dynamics of border migrations and their incidence in the collection of the tariff of Zofratacna, period 2010-2016 - Sosa Joaquín, Yessenia (2018)
The main objective of this research study is to analyze the structure of border migration dynamics and its impact on the collection of the ZOFRATACNA tariff, 2010-2016 period. Correlational research that aims to demonstrate whether the behavior of border migration dynamics has an impact on the collection of the ZOFRATACNA tariff in the 2010-2016 period projected towards 2019. The evolution of the quarterly collection of the special tariff 6%, expressed in thousands of dollars, period 2010-2016 and its projection to 2019 has a decreasing trend. The collection of the special tariff of 6% is not related to the dynamics of border migrations. The ZOFRATACNA has not planned in its management documents the strategies, plans, activities that are aimed at identifying the "business for its customers -users", neither to know the tastes and preferences of the "consumers with purchasing power" that visits the Commercial area of Tacna (street markets). There is a high rotation of the managerial cadres of the organic units. There is a 6% dropout rate of current user-clients, in the last 3 years. The entry of merchandise from Chile, to the Commercial Zone of Tacna, represents on average 35% of the total imports, generating a high dependence.